Hubungan Keseimbangan Kerja dan Kehidupan Pribadi dengan Kesehatan Mental Perawat di IGD RSUD Meuraxa Kota Banda Aceh Tahun 2025 - M. Ari Munazar; Agustina Agustina; Tiara Mairani (Yayasan Literasi Sains Indonesia, 2026)
Nurses' mental health is influenced by the balance between work and personal life demands. This imbalance can increase the risk of depression, anxiety, and stress, especially for Emergency Department (ED) nurses who work under high pressure and dynamic conditions. Mental health disorders in nurses not only impact the well-being of healthcare workers but also affect the quality of care and patient safety. This study aims to determine the relationship between work-life balance and levels of depression, anxiety, and stress among ED nurses at Meuraxa Regional Hospital, Banda Aceh, in 2025. The study used a quantitative method with a descriptive analytical approach and a cross-sectional design. The study population was all 42 ED nurses at Meuraxa Regional Hospital, working three shifts, using a total population technique. Data collection was conducted from August 20–23, 2025, using an online Google Form questionnaire. Data analysis used the Fisher's Exact Test in SPSS. The results showed that 28.6% of respondents experienced depression, 83.3% experienced anxiety, and 19.0% experienced stress. Most respondents had a balanced work-life balance (64.3%) and an unbalanced personal life (66.7%). Bivariate analysis showed a significant association between work-life balance and depression (p=0.001), anxiety (p=0.031), and stress (p=0.001). Personal life was significantly associated with stress (p=0.026), but not with depression and anxiety. This study concluded that work-life balance plays a significant role in maintaining the mental health of emergency room nurses.